2019
DOI: 10.1093/mnras/stz032
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the astrophysics of reionization and cosmic dawn from galaxy luminosity functions and the 21-cm signal

Abstract: The properties of the first galaxies, expected to drive the Cosmic Dawn (CD) and the Epoch of Reionization (EoR), are encoded in the 3D structure of the cosmic 21-cm signal. Parameter inference from upcoming 21-cm observations promises to revolutionize our understanding of these unseen galaxies. However, prior inference was done using models with several simplifying assumptions. Here we introduce a flexible, physicallymotivated parametrization for high-z galaxy properties, implementing it in the public code 21… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
279
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(328 citation statements)
references
References 155 publications
26
279
0
Order By: Relevance
“…Nevertheless despite some degenerate effects on the 21cm global signal among the amplitude of primordial fluctuations and astrophysical parameters, they can be removed by combining other observations. Actually a recent analysis [22] has shown that the combination of 21cm power spectrum and UV luminosity function can severely constrain some of the astrophysical parameters, which can reduce the degeneracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless despite some degenerate effects on the 21cm global signal among the amplitude of primordial fluctuations and astrophysical parameters, they can be removed by combining other observations. Actually a recent analysis [22] has shown that the combination of 21cm power spectrum and UV luminosity function can severely constrain some of the astrophysical parameters, which can reduce the degeneracy.…”
Section: Discussionmentioning
confidence: 99%
“…The 21cm signal is observed as an absorption when T S is lower than T CMB , and becomes an emission once the gas is heated sufficiently by the X-ray photons and T s gets larger than T CMB . For the analysis in this paper, we use the latest version of 21cmFAST [22,23] for calculating the 21cm line global signal, which we briefly describe here. The 21cmFAST solves the reionization, the evolution of the spin temperature and evaluate the 21cm brightness temperature distribution.…”
Section: CM Global Signal and 21cmfastmentioning
confidence: 99%
See 1 more Smart Citation
“…More complex astrophysical processes can also enable such a period as well -for example, strong photoheating feedback can delay reionization relative to X-ray heating [47]. Whether this is more than speculation remains uncertain: calibrating the X-ray luminosity of star-forming galaxies to local measurements suggests that the reionization epoch may overlap with the X-ray heating epoch [48,57], but if the EDGES measurement is confirmed, heating must actually occur very early in the Cosmic Dawn, well before reionization is complete.…”
Section: Isolating the Matter Power Spectrummentioning
confidence: 99%
“…Many efforts are now underway to simulate galaxy formation using ab initio cosmological simulations [153,130,63,108,54], rather than using analytic or semianalytic models. However, doing so self-consistently in statistically representative volumes is exceedingly computationally challenging, as a result, semi-analytic and semi-empirical prescriptions for star formation in reionization modeling remain the norm in 21-cm modeling codes [94,110,101]. Though such approaches lack the spatial resolution to model individual galaxies or even groups of galaxies, including some information about the galaxy population permits joint modeling of 21-cm observables as well as high-z galaxy luminosity functions, stellar mass functions, and so on, and thus open up the possibility of tightening constraints on the properties of galaxies using a multi-wavelength approach.…”
Section: Physical Arguments For Inferred Behavior Of F *mentioning
confidence: 99%